2021
DOI: 10.1002/ecy.3478
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and environmental context shape the differential effects of a facilitator in its native and invaded ranges

Abstract: Non-indigenous species often exhibit disproportionately strong negative effects in their introduced range compared to their native range, and much research has been devoted to understanding the role of shared evolutionary history, or lack thereof, in driving these differences. Less studied is whether non-indigenous species, particularly those that are important as facilitators in their native range, have persistent positive effects in their invaded range despite a lack of a shared evolutionary history with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…The demonstration of behavioral regulation is comparatively understudied in the marine realm (Pinsky et al, 2019); however, coastal and pelagic marine species, especially mobile ones, can behaviorally thermoregulate through aestivation (Marshall et al, 2015), microhabitat use (Dong et al, 2017; Gilman et al, 2015), and vertical migration patterns (Nay et al, 2015). Shaded microhabitats, such as rock crevices and barnacle beds, can provide thermal refugia during periods of emersion when temperatures in sun‐exposed microhabitats surpass sublethal and lethal thresholds (Dong et al, 2017; Hesketh et al, 2021). The importance of microhabitats has prompted calls to forecast species range shifts based on available thermal refugia temperatures (e.g., Pinsky et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demonstration of behavioral regulation is comparatively understudied in the marine realm (Pinsky et al, 2019); however, coastal and pelagic marine species, especially mobile ones, can behaviorally thermoregulate through aestivation (Marshall et al, 2015), microhabitat use (Dong et al, 2017; Gilman et al, 2015), and vertical migration patterns (Nay et al, 2015). Shaded microhabitats, such as rock crevices and barnacle beds, can provide thermal refugia during periods of emersion when temperatures in sun‐exposed microhabitats surpass sublethal and lethal thresholds (Dong et al, 2017; Hesketh et al, 2021). The importance of microhabitats has prompted calls to forecast species range shifts based on available thermal refugia temperatures (e.g., Pinsky et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, N. ostrina, a congener species that inhabits higher intertidal regions than N. lamellosa, alters its foraging behavior to avoid high aerial thermal stress and thus reduces its overall vulnerability to aerial warming due to climate change (Hayford et al, 2015(Hayford et al, , 2021(Hayford et al, , 2018. However, the growing unpredictability of extreme thermal events complicates the reliability of accessing microhabitats and altering foraging behavior, especially when temperatures in thermal refugia surpass thresholds (Harley et al, 2023, in preparation), cause mortality of biogenic microhabitats (Hesketh et al, 2021), or reduce windows of opportune foraging conditions (Dong et al, 2017).…”
Section: Parametermentioning
confidence: 99%
“…Impaired larval performance under ALAN is likely to affect not only population health and distribution but also their role as habitat-forming ecosystem engineers. Sessile fauna like our model organisms, the mussel Mytilus edulis and the barnacle Austrominius modestus , support other species by providing three-dimensional habitats [24,30]. As filter feeders with a complex life-cycle involving a larval phase, they couple benthic pelagic systems and contribute to energy flows through trophic chains [5] and the accumulation of calcium and carbon [2,31].…”
Section: Discussionmentioning
confidence: 99%
“…Even if thermal stress is lower beneath shades, low light may have limited algal growth (Pardal‐Souza et al, 2017), preventing the benefit of reduced temperatures from becoming apparent. High intertidal acorn barnacles tend to facilitate a greater abundance of fleshy macroalgae in the northeast Pacific (Hesketh et al, 2021), so an effect of barnacle removal on algae may also have been observed with a longer experiment. Furthermore, the generally low prevalence of algae in terms of both cover (0%–20% cover) and diversity (six species present) at this site may have prevented the detection of any treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to affecting temperature, heatwaves also increase desiccation stress (Straub et al, 2019), which barnacles may mitigate by retaining moisture. For example, in the desiccating environment of Argentinian Patagonia, areas with moisture‐retaining barnacles host a greater abundance of pulmonate limpets than areas without barnacles (Hesketh et al, 2021). However, we do not fully know if there is an upper threshold of abiotic stress above which such positive interactions weaken or cease entirely.…”
Section: Introductionmentioning
confidence: 99%